Licogliflozin versus placebo in women with polycystic ovary syndrome: A randomized, double‐blind, phase 2 trial. Issue 11 (27th July 2021) - Tan, Susanne; Ignatenko, Stanislav; Wagner, Frank; Dokras, Anuja; Seufert, Jochen; Zwanziger, Denise; Dunschen, Karin; Zakaria, Marjorie; Huseinovic, Neda; Basson, Craig T.; Mahling, Ping; Fuhrer, Dagmar; et al.
Abstract: Polycystic ovary syndrome (PCOS) is characterized by hyperandrogenism and insulin resistance. The dual sodium‐glucose co‐transporter 1/2 inhibitor (SGLT1/2i) licogliflozin (LIK066) ameliorates hyperinsulinism in patients with diabetes and obesity. This study examines the effect of licogliflozin on androgens in women with PCOS. In a multicentre, randomized, placebo‐controlled, double‐blind, 2‐week trial, patients with PCOS received licogliflozin 50 mg or placebo three times a day (TID). Changes in free testosterone (FT), other androgens and variables of insulin resistance were analysed. Concentration of FT did not change (TRLIK066 :TRPCB [FT]: 0.88; 90% CI: 0.70‐1.11; P = .353). Licogliflozin reduced androstendione (A4) by 19% (TRLIK066 :TRPCB [A4]: 0.81; 90% CI: 0.68‐0.99; P = .089) and dehydroepiandrosteron sulphate (DHEAS) by 24% (TRLIK066 :TRPCB [DHEAS]: 0.76; 90% CI: 0.65‐0.89; P = .008). Hyperinsulinaemia was reduced by 70% by licogliflozin (highest insulin concentration [MAXI]; TRLIK066 :TRPCB [MAXI]: 0·26; 90% CI:0.20‐0.34; P < .001 and area under the curve insulin [AUCI]; TRLIK066 :TRPCB [AUCI]: 0.32; 90% CI: 0.25‐0.41; P < .001). Diarrhoea and nausea occurred as common adverse events. Dual inhibition of SGLT1/2 ameliorates hyperinsulinaemia and hyperandrogenaemia in women with PCOS. Licogliflozin may represent a promising novel treatment option for PCOS.